Improving Students' Writing Ability of Procedural Texts by Using Picture Media at Grade VIII SMP Negeri 8 Padangsidimpuan - Yasfin Vizaldi Limbong; Rahmat Huda; Happy Sri Rezeki Purba; Nur Mailiana; Ikhwan Fauzi Nasution; Abdulkarim Duerawee (CV. Alfa Pustaka, 2026)
This research aimed to improve the procedural text writing ability of Grade VIII students at SMP Negeri 8 Padangsidimpuan through the use of picture media. The study was prompted by the students' low proficiency in writing, particularly in composing procedural texts. To address this issue, a Classroom Action Research (CAR) method was employed over two cycles. The subjects of this research were 20 Grade VIII students. Data was collected through writing tests administered in the pre-cycle, Cycle I, and Cycle II stages. The results showed a significant improvement after the implementation of picture media. In the pre-cycle stage, only one student (5%) achieved the Minimum Mastery Criteria (KKM). This number increased to five students (25%) by the end of Cycle I. The most significant improvement occurred in Cycle II, where 13 students (65%) successfully reached the KKM. This consistent improvement from 5% to 65% demonstrates that using picture media was effective in enhancing the procedural text writing ability of Grade VIII students at SMP Negeri 8 Padangsidimpuan.).